Seasonal dynamics of physiological response in Sahiwal cows adapted to hot-arid climate of Rajasthan state - Gayatri Gujar,; Prince Vivek,; VK Choudhary,; Monika Sodhi,; Amandeep,; Nampher Masharing,; Manish Tiwari,; Manishi Mukesh, (Journal of Livestock Biodiversity, 2025)
A total of 50 Sahiwal cows totalling to a cumulative of 400 physiological observations, reared in the hot-arid region of Bikaner district in Rajasthan were evaluated for seasonal effects on their physiological response. All the evaluated physiological parameters viz rectal temperature (RT), respiration rate (RR), pulse rate (PR), skin temperature (ST) at ventral (VT), dorsal (DT) and lateral (LT) points of cows revealed a seasonal effect, however the changes were not pathological nor very adverse. The maximum values for all parameters under study were recorded during the afternoon time points in summer and hot-humid seasons, showing a positive effect of THI on these parameters.